Development of fast dispersing tablets of nebivolol: experimental and computational approaches to study formulation characteristics (Brazilian Journal of Pharmaceutical Sciences, 2014)
Formulation of FDT (fast dispersing tablets) of nebivolol was optimized and evaluated using simplex lattice design (SLD). The influence of type and concentration of three disintegrants viz., Ac-Di-Sol, Primojel and Polyplasdone XL on hardness, friability and disintegration time of tablet was studied. Response surface plot and the polynomial equations were used to evaluate influence of polymer on the tablet properties. Results were statistically analyzed using ANOVA, and a p < 0.05 was considered statistically significant. Results reveal that fibrous integrity and optimal degree of substitution in Primojel and Ac-Di-Sol are mainly responsible for the hardness of the tablet. Use of Polyplasdone in higher percentage in tablet formulation may result in high friability. Increase in concentration of Ac-Di-Sol increases the disintegration time but increased concentration of Primojel in the tablet formulation decreases the disintegration time. This is also evident from model terms for disintegration time with a high 'F' value of 14.69 and 'p' value of 0.0031 (